ANALYSIS OF THEME AND RHEME IN OPINION AND IDEA OF ANALYTICAL EXPOSITION TEXTS WRITTEN BY THE ELEVENTH GRADERS OF SMA N 4 MAGELANG IN THE SCHOOL YEAR OF 2018/2019 - Ernia Dwi Apsari (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2019)
One of the important skills to be mastered by the students in learning English is writing skill because it is used to construct an academic text. However, most of the students have difficulties in writing process that will cause them do not produce texts as it should be. The term of textual meaning refers to theme and rheme. Theme and rheme can be used to make a well-organized paragraph in writing.The objectives of this research are to find out the realization of theme and rheme and the types of theme in opinion and idea of analytical exposition texts written by the eleventh graders of SMA N 4 Magelang in the school year of 2018/2019. The subject of this research is the students of XI Science 4 grade of SMA N 4 Magelang in the school year 2018/2019.The type of this research is descriptive qualitative, it allows the writer to make a personal assessment in form of descriptive text. Based on Gerot and Wignell’s theory (1994), there are three types of theme. They are topical theme that consists of marked and unmarked topical theme, then interpersonal theme, and textual theme. The result shows that marked topical theme has the lowest percentage, it is 2.47%. The first mostly applied theme is unmarked topical theme that has 50%. Textual theme has second range that is 38.27%. The last is interpersonal theme, showing the judgment of person, has 9.26% out of 100% percentage of theme.